How stroke-related dysphagia relates to quality of life: the mediating role of nutritional status and psychological disorders, and the moderating effect of enteral nutrition mode - Zeng, Hongji; Zeng, Xi; Xiong, Nana; Wang, Lichun; Yang, Ying; Wang, Liugen; Li, Heping; Zhao, Weijia (Frontiers in Nutrition, 2024)
Abstract Background Although stroke-related dysphagia has been shown to influence quality of life (QOL), the underlying mechanisms have yet to be uncovered. Objective This study aims to investigate the mediating role of nutritional status and psychological disorders in the relationship between stroke-related dysphagia and QOL in stroke patients and explore the moderating effect of enteral nutrition mode. Methods: In 2022, A questionnaire survey using stratified random sampling was conducted on 5322 stroke patients with dysphagia, including Functional Oral Intake Scale (FOIS), Swallowing Quality of Life Questionnaire, Patient Health Questionnaire-9 (PHQ-9), and Generalized Anxiety Disorder-7 (GAD-7) to assess dysphagia, QOL and psychological disorders respectively for each participant. Records of serum albumin, Hemoglobin, Total serum protein, serum prealbumin and Body mass index were enrolled to assess nutritional status. Results: FOIS demonstrated a significant positive predictive effect on QOL. Nutritional status and psychological disorders (PHQ-9 and GAD-7) mediated the relationship between FOIS and QOL. Nutritional status-psychological disorders showed a chain mediation effect in the relationship between FOIS and QOL. The moderating effect of enteral nutrition mode was observed. Conclusion: The mediating role of nutritional status and psychological disorders with moderating effect of enteral nutrition mode in the relationship between dysphagia and QOL in stroke patients was found.